2008
DOI: 10.2478/s11696-008-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous production of citric acid and erythritol from crude glycerol by Yarrowia lipolytica Wratislavia K1

Abstract: This study shows a possible microbial process for utilization of crude glycerol generated by the biodiesel industry for citric acid and erythritol production. Simultaneous production of citric acid and erythritol under nitrogen-limited conditions with glycerol as the carbon source was achieved with an acetate negative mutant of Y. lipolytica Wratislavia K1 in fed-batch cultivations. The effect of the initial glycerol concentration (from 30–180 g dm−3) on the citrate and erythritol production was investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 59 publications
3
62
1
9
Order By: Relevance
“…Effect of the medium pH on the production of erythritol Our recent investigations have shown that an acetatenegative mutant of Y. lipolytica Wratislavia K1, can produce simultaneously high amounts of erythritol and citric acid under nitrogen-limited conditions, with glycerol as the carbon source, at the pH of 5.5, which is optimal for citrate biosynthesis (Rymowicz et al 2008). The effect of the pH of the medium on the production of erythritol by this strain in a glycerol containing medium (total concentration 300 g l -1 ) was examined using media of a pH of 2.5-6.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of the medium pH on the production of erythritol Our recent investigations have shown that an acetatenegative mutant of Y. lipolytica Wratislavia K1, can produce simultaneously high amounts of erythritol and citric acid under nitrogen-limited conditions, with glycerol as the carbon source, at the pH of 5.5, which is optimal for citrate biosynthesis (Rymowicz et al 2008). The effect of the pH of the medium on the production of erythritol by this strain in a glycerol containing medium (total concentration 300 g l -1 ) was examined using media of a pH of 2.5-6.5.…”
Section: Resultsmentioning
confidence: 99%
“…A cost reduction in erythritol production can be achieved by using less expensive substrates. We have recently reported that an acetate-negative mutant of Y. lipolytica Wratislavia K1 has the ability of simultaneously producing high amounts of erythritol and citric acid in media containing glycerol, at pH 5.5 which is optimal for citric acid biosynthesis by Y. lipolytica (Rymowicz et al 2006(Rymowicz et al , 2008. In the current study, we evaluate the dynamics and yield of erythritol production from raw glycerol by the strain Wratislavia K1 at various pH, and thereafter investigate, in fed-batch experiments, the effect of the optimal pH on the production of erythritol by other strains belonging to the species Y. lipolytica.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our earlier studies showed that acetate-negative mutant strains of Y. lipolytica (strains Wratislavia 1.31, Wratislavia AWG7, and Wratislavia K1), cultivated in medium containing glycerol, produced high amounts of citric acid and low quantities of by-product, e.g., isocitric acid. Additionally, we have found that some yeast strains may produce a considerable amount of other by-products, such as erythritol and mannitol on glycerol media (Rymowicz et al , 2008Rywińska et al 2009). …”
Section: Introductionmentioning
confidence: 96%
“…The data obtained are presented in Table 3. When the ratio of glycerol and urea in the composite was in the range of 3:0-3:1, pH of soil ranged from 6.01 to 6 3:0.6 6.01 ± 0.05 5.75 ± 0.10 5.61 ± 0.01 5.71 ± 0.01 6.08 ± 0.11 6.29 ± 0.09 6.24 ± 0.10 6.46 ± 0.02 3:0.8 6.09 ± 0.07 5.87 ± 0.06 5.71 ± 0.02 5.83 ± 0.05 6.24 ± 0.04 6.31 ± 0.10 6.55 ± 0.04 6.64 ± 0.06 3:1 6.06 ± 0.04 5.59 ± 0.28 5.84 ± 0.02 5.90 ± 0.08 6.37 ± 0.07 6.53 ± 0.12 6.66 ± 0.11 6.74 ± 0.11 3:2 6.11 ± 0.07 6.13 ± 0.08 6.36 ± 0.05 6.49 ± 0.05 6.90 ± 0.09 7.17 ± 0.09 7.28 ± 0.03 7.58 ± 0.03 3:3 6.08 ± 0.04 6.45 ± 0.06 6.33 ± 0.03 6.57 ± 0.02 7.12 ± 0.07 7.39 ± 0.11 7.74 ± 0.41 7.85 ± 0.24…”
Section: Ph Analysismentioning
confidence: 99%
“…While the search of applications for low-purity technical glycerol is an urgent problem. The attempts to use crude glycerol as an additive of animal fodder, as a raw material for the production of fuel and chemicals have been reported [3][4][5][6]. Increase of biodiesel production is accompanied by the accumulation of larger amounts of rapeseed cake.…”
Section: Introductionmentioning
confidence: 98%